Antimicrobial efficacy of cinnamon, ginger, horseradish and nutmeg extracts against spoilage pathogens - Mvuemba, Hortense; Green, Sarah; Tsopmo, Apollinaire; Avis, Tyler (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2009)
In the search for alternatives to the use of synthetic fungicides, aqueous spice extracts were evaluated for their effects on the mycelial growth of various spoilage pathogens and their ability to control potato dry rot and carrot cavity spot in vivo. Results showed that cinnamon, ginger and nutmeg significantly inhibited the mycelial growth of Aspergillus niger (Ascomycota), Fusarium sambucinum (Ascomycota), Pythium sulcatum (Oomycota) or Rhizopus stolonifer (Zygomycota), whereas horseradish extract did not lead to the inhibition of any microorganism at the tested concentration. Among the most effective extracts, 0.05 g mL‑1 of cinnamon extract completely inhibited A. niger and P. sulcatum, and 0.10 g mL‑1 of cinnamon extract completely inhibited F. sambucinum. A concentration of 0.05 g mL‑1 of ginger extract also caused 100% inhibition of P. sulcatum. In vivo, cinnamon extract significantly reduced lesions of potato dry rot and carrot cavity spot, and ginger extract reduced lesions of carrot cavity spot. These results indicate that aqueous cinnamon and ginger extracts could provide an alternative to the use of synthetic fungicides to control these pathogens.